The Influence of CIRC Model and Cooperative Script on Listening Learning Achievements in Class XII - Aminatul Qomariyah (Penerbit STKIP PGRI Bangkalan, 2022)
Background of this research is listening teaching model used by teachers are stillteacher’s center and it haven’t given chance for students’development well. Problem in thisresearch is which one more dominant between teaching model of CIRC and Cooperative scriptto result study of XII grade students ?. The purpose of the research is to knowwhich one moredominant between teaching model of CIRC and Cooperative script to result study of XII gradestudents ?. Research method uses Descriptive Quantitative Approach because in this researchuses one variable,sympthom that are researched naturallyand the result will be takenquantitatively. Sampling method that used is cluster sampling. The sample taken just 64 studentsof XII grade SMAN 1 Kwanyar. Analysis method is using Paired sample T - test and one wayANOVA. The formula to look for validity value in the research is Product Moment Correlation(Pearson). Instruments in the research issome questions given orally. Result of the researchbased on first trying hypothesis by using SPSS show result 0,000 < 0,05 it can be concludedthat CIRC model have a significant influencing to studying achievement of listening. Thesecond trying hypothesis also get the same value it means that Cooperative script model alsohas a significant influencing to listening achievement. On the third trying hypothesis by usingone way ANOVA got result value 0,020 < 0,05 So it can be concluded that cooperative scripthas higher influence than CIRC. Mean of using cooperative script is 79,20 while CIRC get mean75,10.